Thermal Efficiency Enhancement of Solar Dryer using Sun Tracking System - borirak, theerapong (Srinakharinwirot University Engineering Journal, 2019)
The solar dryer for food preservation from solar energy to heating the product for evaporate water the thermal efficiency of solar dryer cabinet up to solar energy. This paper concern the study of thermal efficiency of the bananas dryer by the solar drying cabinet size 45 cm x 108 cm x 38.5 cm. and 45° of the mirror angle installation thermometer and humidity meter inside and out side of solar dryer cabinet. Fermented 144 pieces bananas were a product for drying. It was founds from the experiment that, in the duration of 9.00 am – 5.00 p.m. on a clear sky day, and all – day average temperature inside chamber was 46.93°C. The experiment was started from and initial moisture content of bananas of 79.18% wet basis were dried until a final moisture content equaled 29.3% wet basis. For these data to design solar dryer cabinet with sun tracking by DC motor and scissor jack for rotate the solar dryer cabinet. The experiment was tilted conformable of sun light 7.5 degree/ hr. The experiment were dried until a final moisture content equaled 24.8% wet basis and all – day average temperature inside chamber was 52°C. The experiment can decrease time for dryer the bananas from 24 hr to 20.5 hr.